Desarrollo de un sistema web para el proceso de matrícula en línea de la unidad educativa "Carlos Lozada Quintana" en el cantón La Maná. - Carpio Galeas, Thalia Lisbeth (2023)
Currently, computer systems have advanced at significant levels. In this way the Carlos Lozada Quintana Educational Unit, located in La Maná canton, is a private academic institution that feels the need of an online enrollment web system to allow students to get enrolled through the internet, and those in charge of the educational unit keep track of the enrollment for admission to the new school period. For the creation of this web system, it was pertinent to know the enrollment processes carried out by the educative unit through the application of interviews and surveys to establish the functional requirements of the system, which allowed the development of the computer system through high-level development tools and the agile Scrum methodology, essential for the application of black box and white box tests. In such a way, this generated satisfactory results on its functionality with the addition of a domain according to the institution name, allowing the implementation in a hosting and web search. Likewise, the design of a user's manual was held, so that the direct beneficiaries of the research project can use it in the right way.